3D heterostructure Fe3O4/Ni/C nanoplate arrays on Ni foam as binder-free anode for high performance lithium-ion battery. (10th November 2015) - Li, Zhaolin; Zhao, Hailei; Wang, Jie; Lv, Pengpeng; Zhang, Zijia; Zeng, Zhipeng; Xia, Qing
Graphical abstract: Highlights: Self-supported Fe3 O4 /Ni/C electrode is prepared by a hydrothermal route. The electrode presents nanoplate array structure with a 3D conductive network. A high capacity of 832.5 mAh g −1 and an excellent rate-capability are delivered. Abstract: An open-up network structure assembled by interconnected 3D heterostructure Fe3 O4 /Ni/C nanoplate arrays on Ni foam is successfully synthesized via a facile hydrothermal method with subsequent CVD heat treatment. When used as a binder free anode material for lithium-ion battery (LIBs), it shows quite a favorable electrochemical performance with high reversible capacity and good rate capability. A high capacity of 832.5 mAh g −1 is achieved at 0.3C and a specific capacity of 279 mAh g −1 can still be delivered at current density of 4.5C, corresponding to 34% of the capacity at 0.3C. The self-supporting nanoplates are intercrossed and interconnected with robust adhesion on Ni foam, preventing the active material from peeling off during the electrochemical reactions. Ni foam substrate, uniform carbon layer on the nanoplate surface and in-situ formed Ni nanocrystals together play important roles in effectively building a fast 3D electron transport network for electrode reactions. The excellent electrochemical performance makes this composite a promising candidate as anode material for high energy density LIBs.